Environmental disclosure and value creation: empirical evidence from ISO 14001 companies / Afaf Izzati Nafhah Radzi - Radzi, Afaf Izzati Nafhah (2015)
Presently, businesses are urged to be more environmentally and socially responsible in their business operations as such acts are expected to improve corporate performance, which in turn could create value to the organizations. This expectation is more prevalent among companies that have received environmental certification such as ISO 14001. Therefore, the objective of the study is to investigate the influence of internal factors, namely sustainable governance, environmental management system and environmental risk management committee, and external factors such asm government ownership and industry membership on the quality of environmental disclosure among ISO 14001 companies. This study also examined the subsequent effect of such disclosures in creating value to the organizations. The agency and stakeholder theories were used to underpin the arguments for the study. Content analyses of the annual and sustainability reports of ninety (90) ISO 14001 certified companies were undertaken to for the year 2014. The multiple regression analyses were employed for hypotheses testing. The results of the descriptive analysis revealed that the level of environmental disclosure among ISO 14001 certified companies in Malaysia is still low. The results of the multiple regression analyses revealed that internal factors in the form of an effective environmental management system and external pressure such as industry membership provide significant positive relationships with the quality of environmental disclosure. The results also found a positive and significant relationship between the quality of environmental disclosure and value creation. The result of the study is consistent with the certification of ISO 14001 where such certification provides a framework for an effective environmental management system that can facilitate the disclosure of environmental information especially among companies in environmentally sensitive industries. Such environmental disclosures seemed to be welcomed by stakeholders resulting in value creation to the organizations.